Factors Influencing Luxury Fashion Retailers’ Entry Mode Selection: A Case Study of Louis Vuitton in China - Liang, Keqin (2014)
The luxury industry is one of the leading industries in the global financial markets and has surpassed other consumer categories with its remarkable performance. Meanwhile, China is predicted to become the largest luxury market in 2015. Therefore, in line with a buoyant market trend, the leading luxury retailers have shifted their focus to Chinese markets, to seize new market opportunities.